1984
DOI: 10.1002/macp.1984.020081984109
|View full text |Cite
|
Sign up to set email alerts
|

Melt rheology and morphology of polymer blends

Abstract: A b s t r a c t -S i z e s and shapes o f t h e component phases o f i m m i s c i b l e polymer b l e n d s a r e s t r o n g l y i n f l u e n c e d by t h e v i s c o e l a s t i c p r o p e r t i e s o f each component. F o r m i x t u r e s o f d i f f e r e n t poly(ethylene terephthalatels end polyamide-6 i t can be e s t a b l i s h e d t h a t t h e morphology under shear i s t h e r e s u l t o f t h e v i s c o e i t y r a t i o , which d e t e r m i n e s t h e s i z e o f t h e d r o p l e t -p h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 5 publications
3
26
0
1
Order By: Relevance
“…According to the literature, in a shear ow eld, with viscoelasticity ratios (k, k 0 ) > 4, the deformation and breakup of a higher elastic drop in a weakly elastic matrix is not reached, giving rise in the majority of cases to a coarse and heterogeneous morphology. 23,24,42 Nevertheless, the PLA/PA11 systems exhibit a very low interfacial tension at the melt processing temperature (g PLA,PA11 # 0.6 mN m À1 ), which may partially explain the ne morphological structure obtained. In the case of PLA/PA6 extrudate blends, the viscosity and elasticity ratios are higher than 1 due to the weak viscoelasticity of neat PLA compared to PA 6.…”
Section: Morphology Of the Blends In The Extrudatementioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, in a shear ow eld, with viscoelasticity ratios (k, k 0 ) > 4, the deformation and breakup of a higher elastic drop in a weakly elastic matrix is not reached, giving rise in the majority of cases to a coarse and heterogeneous morphology. 23,24,42 Nevertheless, the PLA/PA11 systems exhibit a very low interfacial tension at the melt processing temperature (g PLA,PA11 # 0.6 mN m À1 ), which may partially explain the ne morphological structure obtained. In the case of PLA/PA6 extrudate blends, the viscosity and elasticity ratios are higher than 1 due to the weak viscoelasticity of neat PLA compared to PA 6.…”
Section: Morphology Of the Blends In The Extrudatementioning
confidence: 99%
“…Since the experimental measurements of the normal force N 1 are delicate, most studies devoted to the brillar morphology have focused on the effect of viscosity ratio neglecting the importance of the elasticity ratio between the dispersed and continuous phase, leading to contradictions and ambiguity to draw a clear correlation between the viscosity ratio and the optimal conditions of ber formation and its temporal stability in the case of viscoelastic immiscible polymer blends. [19][20][21][22] According to several literature reports, 1,[23][24][25][26] in the particular case of berlike morphology, the droplet-bril transition could be controlled by the viscosity ratio (k) between the dispersed phase and matrix (a more viscous matrix promotes the breakdown of droplets [27][28][29][30][31] ), the elasticity ratio (k 0 ) between the dispersed phase and matrix (a more elastic matrix promotes deformation and extension of the nodules into brils 14,17,23,[32][33][34][35][36][37][38][39] ) and a compromise between deformation (shear or elongation) and relaxation should be achieved in order to have a stable lamentous morphology.…”
Section: -12mentioning
confidence: 99%
“…With regard to fibril formation of the dispersed phase, White et al [28] reported that fibrils are formed at 0.3 < qd/qc < 1 .o for polyethylene/polystyrene blends. On the contrary, Beger et al [29], who worked on poly(ethy1ene terephthalate)/polyamide blends, reported that fibrils are obtained for qd/vc > 3.7, and for qd/vc 5 1 only droplets were obtained. The conditions for fibril formation thus may not depend entirely on the viscosity ratio.…”
Section: Morphologymentioning
confidence: 92%
“…Other studies have shown a qualitatively similar dependence of particle size on the viscosity ratio with a minimum between 0.1 and 1.0. 14,19,[33][34][35][36][37]39,64 Many of the studies in the literature are concerned with blends where the viscosity ratio is greater than 1; however, in the present case, this ratio is less than 1 due to the high melt viscosity of the polycarbonate matrix materials. Favis found a minimum particle size at a relative torque ratio of approximately 0.25 for blends of polypropylene in a polycarbonate matrix.…”
Section: Effect Of Processingmentioning
confidence: 99%